Glucose Restriction Promotes Osteocyte Specification by Activating a PGC-1α-Dependent Transcriptional Program - Sánchez-de-Diego, Cristina; Artigas, Natalia; Pimenta-Lopes, Carolina; Valer, José Antonio; Torrejon, Benjamin; Gama-Pérez, Pau; Villena, Josep A.; Garcia-Roves, Pablo M.; Rosa, José Luis; Ventura, Francesc (iScience, 2019)
Osteocytes, the most abundant of bone cells, differentiate while they remain buried within the bone matrix. This encasement limits their access to nutrients and likely affects their differentiation, a process that remains poorly defined. Here, we show that restriction in glucose supply promotes the osteocyte transcriptional program while also being associated with increased mitochondrial DNA levels. Glucose deprivation triggered the activation of the AMPK/PGC-1 pathway. AMPK and SIRT1 activators or PGC-1α overexpression are sufficient to enhance osteocyte gene expression in IDG-SW3 cells, murine primary osteoblasts, osteocytes, and organotypic/ex vivo bone cultures. Conversely, osteoblasts and osteocytes deficient in Ppargc1a and b were refractory to the effects of glucose restriction. Finally, conditional ablation of both genes in osteoblasts and osteocytes generate osteopenia and reduce osteocytic gene expression in mice. Altogether, we uncovered a role for PGC-1 in the regulation of osteocyte gene expression. [Display omitted] •Glucose restriction promotes osteocytic gene expression and mitochondrial function•Glucose restriction triggers activation of the AMPK/PGC-1 pathway•Effects of glucose restriction on osteocyte gene expression depend on Ppargc1a/b•Deletion of Ppargc1a/b in osteoblasts and osteocytes leads to osteopenia Molecular Mechanism of Behavior; Molecular Physiology; Specialized Functions of Cells